Raising micropot nursery and crop establishment in main field for improving oilseed productivity: Raising micropot nursery and crop establishment in main field for improving oilseed productivity - SAMPAD R PATRA; MALAY K BHOWMICK; SHANTANU KAR (Journal of Oilseeds Research, 2020)
Micropot method involving raising of nursery seedlings and their subsequent establishment in main field has been emerged as an innovative package of growing these crops under changing climate situation. The method offers multifarious advantages including climate-resilience, timely or even early sowing, reduced seed rate, easy crop establishment, hands-down weed management, shortened crop duration in main field, less incidence of diseases etc.